PENGARUH DESTINATION IMAGE, PERSEPSI HARGA, DAN FASILITAS TERHADAP KEPUTUSAN BERKUNJUNG DI TAMAN MINI INDONESIA INDAH (TMII) - Stevany Rotua Elesa; Suryani Chodidjah (Human Capital Development, 2023)
The purpose of this study was to determine the effect of destination image, perceived price and facilities on visiting decisions at Taman Mini Indonesia Indah. A total of 100 respondents were taken as samples using the Accidental Sampling method. Data analysis research uses multiple linear analysis with the help of IBM Statistics 26 software. The results of the hypothesis using the t test explain that destination image, price perceptions and facilities are proven to have a partial and significant influence on visiting decisions. Furthermore, through the f test it can be seen that destination image, price perceptions and facilities together have an effect on visiting decisions.